2018
DOI: 10.1016/j.lwt.2017.08.090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dry-sausage starter culture and endogenous yeasts on Aspergillus westerdijkiae and Penicillium nordicum growth and OTA production

Abstract: Processed meat products frequently suffer from fungal and mycotoxin contamination, mostly ochratoxin A (OTA). Penicillium nordicum is considered responsible for this contamination, but Aspergillus westerdijkiae has recently been associated with high levels of OTA in meat products. Several biocontrol agents have been tested against P. nordicum growth and OTA production in meat products, but A. westerdijkiae has not been considered. The aim of this work was to evaluate in vitro the effect of a commercial starter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 42 publications
5
50
0
Order By: Relevance
“…Biocontrol is one of the most effective techniques of controlling various mycotoxins; it uses safe microorganisms in fermented pastes to inhibit pathogen growth [67]. The advantage of the biocontrol method is that the growing conditions of related antagonistic microorganisms are simple enough, and they have strong abilities to multiply in foods for long periods of time [68].…”
Section: Biocontrol Methodsmentioning
confidence: 99%
“…Biocontrol is one of the most effective techniques of controlling various mycotoxins; it uses safe microorganisms in fermented pastes to inhibit pathogen growth [67]. The advantage of the biocontrol method is that the growing conditions of related antagonistic microorganisms are simple enough, and they have strong abilities to multiply in foods for long periods of time [68].…”
Section: Biocontrol Methodsmentioning
confidence: 99%
“…Given its relatively low detection, A. westerdijkiae has rarely been studied as a potential risk of OTA contamination in ripened meat products. Nonetheless, A. westerdijkiae has been recently reported to be well adapted to dry-cured ham and other ripened meat products (Vipotnik et al 2017;Meftah et al 2018;Merla et al 2018), and should be considered a high sanitary risk in products of animal origin with high salt content, such as dry-cured ham (Vipotnik et al 2017).…”
Section: Mycobiota Of Meat Samplesmentioning
confidence: 99%
“…More recently, Merla et al (2018) reported 10% (13) of OTA-contaminated samples from Italian salami and, with the exception of one sample, samples contaminated with A. westerdijkiae showed the highest levels of OTA contamination. In two previous reports (Vipotnik et al 2017;Meftah et al 2018), it was possible to determine the strong ability of this species to produce OTA in dry-cured meat products under a wide range of environmental conditions. More than that, these studies showed that this fungus produces OTA in much higher levels and in a wider range of temperature and water activity than the widely studied P. nordicum, and its ochratoxigenic ability can be stimulated by the presence of other existing or added microbiota (Meftah et al 2018).…”
Section: Mycotoxin Contamination Of Meat Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most effective way to avoid contamination of foods with aflatoxins is to inhibit the growth of A. flavus in these foods (Meftah et al 2018). However, the use of chemical preservatives and fungicides increases the development of resistant fungal strains and negatively impacted on the environment and human health (Droby et al 2009).…”
Section: Introductionmentioning
confidence: 99%